Intravoxel incoherent motion imaging for assessment of bone marrow infiltration of monoclonal plasma cell diseases - Shah, Rajiv; Stieltjes, Bram; Andrulis, Mindaugas; Pfeiffer, Ruth; Sumkauskaite, Migle; Delorme, Stefan; Schlemmer, Heinz-Peter; Goldschmidt, Hartmut; Landgren, Ola; Hillengaß, Jens (Annals of hematology, 2013)
Modern imaging techniques have demonstrated that monoclonal plasma cell diseases infiltrate the bone marrow in a diffuse, focal, mixed pattern. While focal lesions can be easily counted and measured, the diffuse lesions of the infiltration are hard to assess. We therefore investigated 31 patients with monoclonal plasma cell diseases of all stages with intravoxel incoherent motion imaging of the same region of the pelvis from where afterwards a biopsy was obtained. We found a significant correlation between plasma cell percentage in bone marrow histology and the imaging parameters “apparent diffusion coefficient” and the diffusion coefficient D. Furthermore, those parameters correlated with other factors of disease activity, e.g., monoclonal protein, hemoglobin, and immunoparesis. In summary, we found that the non-invasively acquired imaging parameters correlated with the degree of plasma cell infiltration in the bone marrow.